Quantitative analysis of MWCNT agglomeration in polymeric‐based membranes using atomic force microscope. (10th June 2016) - Basri, Hatijah; Irfan, Masooma; Irfan, Muhammad; Lau, Woei‐Jye; Kartohardjono, Sutrasno
Abstract : In this work, we performed an analysis on the surface properties of polyethersulfone (PES)‐based ultrafiltration membranes that were prepared by incorporating acid functionalized multiwalled carbon nanotube (f‐MWCNT) and polyvinylpyrrolidone into membrane matrix via simple blending method. The bonding‐chemistry of the nanocomposites implanted within the PES membrane was investigated by Fourier transform infrared spectrometer while atomic force microscope was employed to observe the distribution of f‐MWCNT in the membrane matrix and further measured its agglomeration quantitatively. The resultant 3D atomic force microscope images provided the most satisfactory way to examine the distribution of nanomaterials in the membranes, and with the help of 'point profile data' the maximum height and width of the agglomerated cluster could be quantitatively calculated. Moreover, the surface profile studies of the membrane surface provided the information about the length, volume, area, perimeter, radius and diameter of grains. It was observed that PES/nanocomposite blended membranes were held together via strong hydrogen bonding, but poor dispersion of MWCNT in the membrane matrix reduced the membrane performance in terms of protein (pepsin and bovine albumin serum) rejection and increased the surface roughness. Copyright © 2016 John Wiley & Sons, Ltd.